The Effectiveness of The Fundraising Strategy for ZIS (Zakat, Infaq, and Sadaqah) Through Fintech Payment at BAZNAS (The Amil Zakat National Agency) of The Special Region of Yogyakarta - Nurhardiansyah, Achmad; Adha, Mufti Alam; Wahyudi, Rofiul (JURNAL EKONOMI SYARIAH, 2025)
Introduction to The Problem: Effectiveness is the success of the institution in determining the failure of the organization to its objectives. This research is a field research with a descriptive qualitative approach. The object of this research is the effectiveness of fund-raising strategies through fintech. The data collection techniques performed by researchers are observations, structured interviews, documentation and triangulation. The results of this research are known ZIS payments through fintech in 2020 to 2022 experienced a significant increase, in 2020 reached 26.7% and in 2021 reached 34.5% and in 2022 collection through fintech 37.9% so that it can be concluded that ZIS payment through Fintech effectively implemented.Purpose: The aim of this research is to find out the effectiveness of ZIS fund-raising strategies through the use of fintech technology in BAZNAS in Yogyakarta Special District.Design/methodology/approach: This research is a field research with a descriptive qualitative approach. The object of this research is the effectiveness of fund-raising strategies through fintech. The data collection techniques performed by researchers are observations, structured interviews, documentation and triangulation.Findings: The results of this research are known ZIS payments through fintech in 2020 to 2022 experienced a significant increase, in 2020 reached 26.7% and in 2021 reached 34.5% and in 2022 collection through fintech 37.9% so that it can be concluded that ZIS payment through Fintech effectively implemented.Research Implication: The use of digital technology over financial technology can have a significant impact in terms of fund-raising because fintech provides transaction ease, transaction speed and transaction security.Originality/value: This research contributes to maximizing the use of digital technology in the financial sector specifically in the ZIS launched by BAZNAS. This research aims to examine how effective the use of financial technology is to collect zakat funds from muzakki. The use of data collection techniques through interviews provides a clearer and more real picture. This research is very important for the BAZNAS institution to increase the collection of zakat funds from muzakki and maximize zakat funds for mustahik.Reseacrh Type: Research Article